What is Geography? - Bonnett, Alastair (Lanham Rowman & Littlefield, 2023)
Geography is fundamental to understanding the way the world works. This text offers readers a short and highly accessible account of the ideas and concepts constituting geography. Including discussion of both the human and the natural realms, the text looks at key themes such as environment, space, and place$1 (Bas well as geography's methods and the history of the discipline$1 (Bshowing us how and why they are essential for a thriving planet.s
Keywords: Environmental Geography; Social Science / Social Geography; Cultural Geography